A transportable, inexpensive electroporator for in utero electroporation. (19th May 2015) - Bullmann, Torsten; Arendt, Thomas; Frey, Urs; Hanashima, Carina
<x xml:space="preserve">Abstract</x> Electroporation is a useful technique to study gene function during development but its broad application is hampered due to the expensive equipment needed. We describe the construction of a transportable, simple and inexpensive electroporator delivering square pulses with varying length and amplitude. The device was successfully used for in utero electroporation in mouse with a performance comparable to that of commercial products.